2004
DOI: 10.1021/jf035445w
|View full text |Cite
|
Sign up to set email alerts
|

2-O-(β-d-Glucopyranosyl)ascorbic Acid, a Novel Ascorbic Acid Analogue Isolated from Lycium Fruit

Abstract: A novel stable precursor of ascorbic acid (vitamin C), 2-O-(beta-D-glucopyranosyl)ascorbic acid, was isolated from both the ripe fresh fruit and dried fruit of Lycium barbarum L., a plant of the Solanaceae family. The chemical structure was inferred by instrumental analyses and confirmed by chemical synthesis. The dried fruit of Lycium barbarum L. contained ca. 0.5% of it, which is comparable to the ascorbic acid content of fresh lemons. It increased the blood ascorbic acid by oral administration to rats, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 6 publications
2
64
0
1
Order By: Relevance
“…Present address: Faculty of Life and Environmental Sciences, Prefectural University of Hiroshima, Shobara 727-0023, Japan; Fax: +81-824-74-1779; E-mail: atai@pu-hiroshima.ac.jp AA-2G to rats increased the level of AA-2G as well as AA in the blood of the portal vein, probably due to lesser distribution of -glucosidase than of -glucosidase. 19) Thus, if AA-2G per se possesses antioxidant activity as dose AA-2G, it might contribute to antioxidant defense in the body. As far as we know, there have been no reports on the antioxidant activities of AA-2G.…”
Section: Abstract: 2-o--d-glucopyranosyl-l-ascorbicmentioning
confidence: 99%
“…Present address: Faculty of Life and Environmental Sciences, Prefectural University of Hiroshima, Shobara 727-0023, Japan; Fax: +81-824-74-1779; E-mail: atai@pu-hiroshima.ac.jp AA-2G to rats increased the level of AA-2G as well as AA in the blood of the portal vein, probably due to lesser distribution of -glucosidase than of -glucosidase. 19) Thus, if AA-2G per se possesses antioxidant activity as dose AA-2G, it might contribute to antioxidant defense in the body. As far as we know, there have been no reports on the antioxidant activities of AA-2G.…”
Section: Abstract: 2-o--d-glucopyranosyl-l-ascorbicmentioning
confidence: 99%
“…L-ascorbyl Phosphate (VCP-IS-Na) 2 4 1 Synthesis of 5, 6-O-isopropylidene ascorbic acid The synthesis of 5,6-O-isopropylidene-ascorbic acid was carried out in the manner similar to that in the previous methods (22,23 (24). To a solution of phosphorus oxychloride (13.8 g, 0.09 mol) in toluene (54 mL) was added dropwise isostearyl alcohol (24.4 g, 0.09 mol) and triethylamine (9.1 g, 0.09 mol).…”
Section: Preparation Of Sodium Isostearyl 2-o-mentioning
confidence: 99%
“…Although Toyoda-Ono et al tried to synthesize AA-2G by a chemical approach, they found that the procedure was too complicated and was thus unsuitable for large-scale production (Toyoda-Ono et al 2004).…”
Section: Production Of Aa-2g By Biotransformationmentioning
confidence: 99%